DISKRIMINASI SOSIAL DALAM NOVEL ORANG CACAT DILARANG SEKOLAH KARYA WIWID PRASETYO - Fauzi, Rian; Thahar, Harris Effendi; Asri, Yasnur (Universitas Negeri Padang, 2012)
The purpose of this study was (1) to describe a form of social discrimination contained in novel Orang Cacat Dilarang Sekolah by Wiwid Prasetyo Â and (2) Describe the causes of social discrimination in the novel Orang Cacat Dilarang Sekolah by Wiwid Prasetyo . The data source of this research is novel Orang Cacat Dilarang Sekolah by Wiwid Prasetyo . Data collected by descriptive methods. The findings of the research that forms and causes of social discrimination in the novel Orang Cacat Dilarang Sekolah by Wiwid Prasetyo